2020
DOI: 10.2196/19126
|View full text |Cite
|
Sign up to set email alerts
|

Information Overload in Emergency Medicine Physicians: A Multisite Case Study Exploring the Causes, Impact, and Solutions in Four North England National Health Service Trusts

Abstract: Background Information overload is affecting modern society now more than ever because of the wide and increasing distribution of digital technologies. Social media, emails, and online communications among others infuse a sense of urgency as information must be read, produced, and exchanged almost instantaneously. Emergency medicine is a medical specialty that is particularly affected by information overload with consequences on patient care that are difficult to quantify and address. Understanding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Interviewee 1099 (ICU Consultant) also raised concerns regarding notifications or alerts coming in at inappropriate times, since this could cause the adverse effect of “demoralizing people.” This participant further mentioned a concern for having a tool with which staff could compare their unit target achievements with other units. This could increase ICU staff stress, and might lead to suffering from burnout or cognitive overload, “wow, mine’s [targets or parameters] all red, things aren’t going very well,” which could have ramifications for both patients and staff due to the well-documented fact that the ICUs are incredibly stressful environments [ 5 , 6 , 52 ]. These are important concerns to address early and to ensure staff are all fully informed regarding the system itself and the transparency regarding how the digital logs that it will produce may be used outside of patient monitoring (eg, can these be used to assess staff performance in the workplace?).…”
Section: Resultsmentioning
confidence: 99%
“…Interviewee 1099 (ICU Consultant) also raised concerns regarding notifications or alerts coming in at inappropriate times, since this could cause the adverse effect of “demoralizing people.” This participant further mentioned a concern for having a tool with which staff could compare their unit target achievements with other units. This could increase ICU staff stress, and might lead to suffering from burnout or cognitive overload, “wow, mine’s [targets or parameters] all red, things aren’t going very well,” which could have ramifications for both patients and staff due to the well-documented fact that the ICUs are incredibly stressful environments [ 5 , 6 , 52 ]. These are important concerns to address early and to ensure staff are all fully informed regarding the system itself and the transparency regarding how the digital logs that it will produce may be used outside of patient monitoring (eg, can these be used to assess staff performance in the workplace?).…”
Section: Resultsmentioning
confidence: 99%
“…Information overload in perioperative medicine is a major concern. 41 New monitoring strategies, which integrate different information sources in one straightforward, visual model could help to reduce information overload. The neurocardiovascular graphs provided new information on how the neonatal physiology and the CBF regulation mechanisms are affected by the actions of the clinicians, even in the most cardiore-spiratory stable patients.…”
Section: Discussionmentioning
confidence: 99%
“…I wouldn't be focused on what's important." Evidence shows that doctors are also profoundly affected by an ever-increasing amount of medical information impacting every aspect of their job (Sbaffi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, excessive and unnecessary information can lead to anxiety and cognitive load, making it challenging to retrieve critical information. In 2016 a survey conducted by the Pew Research Center survey (Sbaffi, Walton, Blenkinsopp, & Walton, 2020) reported that about 20% of the American population experience information overload and face difficulty in searching for important information. Families in our study noted, "I don't necessarily want to see that information.…”
Section: Discussionmentioning
confidence: 99%